Rural Agro-Enterprise Partnership for Inclusive Development and Growth (RAPID-Growth) Project Baseline Survey - Roehlano M. Briones; Adoracion M. Navarro; Michael Ralph M. Abrigo; Anna Jennifer L. Umlas; Jokkaz S. Latigar (Philippine Institute for Development Studies (PIDS), 2023)
This study presents a baseline survey for the Rural Agro-enterprise Partnership for Inclusive Development and Growth (RAPID-Growth) project implemented by the Department of Trade and Industry. Operating in six regions of Mindanao and Region VIII, the project focuses on key value chains, including cacao, coconut, coffee, and processed fruits and nuts. The study delves into the current conditions of smallholder farming households and Farmer Organizations (FOs), complementing another PIDS study on matching grants as a strategy for enterprise development (Umlas and Briones 2023). Utilizing quantitative impact evaluation and process evaluation, the research undertakes the first step towards assessing program effects and understand program implementation. Survey key findings underscore the alignment of the treatment group with project selection criteria, particularly from high-poverty municipalities and vulnerable groups. Some differences between the treatment and control groups are already evident in terms of income sources, economic enterprise participation, and credit access, which needs to be carefully considered when isolating project impact at the endline. The enterprise profiling reveal that the majority of involved FOs are larger entities with over 200 members, operating for 0-9 years, and comprising of cooperatives, corporations, and worker associations. Despite challenges, such as the absence of a robust M&E system, the process evaluation highlights positive aspects including the effectiveness of the matching grant scheme, FO empowerment, FO capacity development, and private sector involvement. Finally, baseline study recommendations relate to expediting project completion, reconsidering certain project components, and enhancing technical assistance to FOs.
Keywords: 330; smallhold farmers; farmer organizations; enterprise development; agricultural value chain; matching grant; baseline study; impact evaluation; process evaluation